2022
DOI: 10.7584/jktappi.2022.12.54.6.94
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fuel Pellets Made by Mixing Paper Sludge and Forest Byproducts

Abstract: In this study, for reusing the sludge generated in a fine paper mill as fuel, the characteristics of the pellets prepared by mixing auxiliary raw materials such as pulp mill chip rejects, camellia oilseed cake, Sancho pruning remnants, and mulberry pruning remnants were evaluated. The pellet yield decreased as more sludge containing about 50% of the inorganic fillers was mixed with each auxiliary material, but the camellia oilseed cake, unlike the others, was of great help in improving the pellet yield. The Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…It can be co-fired with other fuels in power plants or used in the production of biofuels. Some studies have also demonstrated that PMS can be economically used as a raw feedstock for producing solid fuels when appropriately mixed with other woody biomasses in suitable proportions [21,22]. Furthermore, some studies have shown that PMS mixed with old newspaper (ONP) can be used to create biodegradable seedling pots for replacing plastic pots [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It can be co-fired with other fuels in power plants or used in the production of biofuels. Some studies have also demonstrated that PMS can be economically used as a raw feedstock for producing solid fuels when appropriately mixed with other woody biomasses in suitable proportions [21,22]. Furthermore, some studies have shown that PMS mixed with old newspaper (ONP) can be used to create biodegradable seedling pots for replacing plastic pots [23][24][25].…”
Section: Introductionmentioning
confidence: 99%